ANALYSIS OF HAZE FREE IMAGES AND REMOVAL OF FOG USING DARKCHANNEL PRIOR ALGORITHM - jyothi, S. Vyshnavi; Bharathi, P.Shyamala (International Journal of Psychosocial Rehabilitation, 2020)
In this technology world there are various applications are used to for the image filtration for the clarity and the quality of the image. When the image get reconstructed the size of the image is get increased so the need large storage space. It needs some processing time to convert the image. In this paper they propose the conventional haze removal method it can changes the contrast and saturation of the image. By removing the haze it can changes the luminance of the image to wider range. To avoid the problem we propose a method that can maintain the luminance value equal to that of the contrast. The luminance value can be adjusted to the minimum level which is equal to that of the other methods of brightness control. The atmospheric condition can be monitored at the time of capturing the image based on the atmospheric parameters such as the light illumination level and other noise. Based upon the observed parameters the image can be adjusted. The reconstruction of the image can need less time to process it takes 0.56 seconds a single pixel of image. The proposed haze removal method can give the better contrast image and the quality of the image is effective when compared to other methods. The accuracy is about 85%.